PENGARUH PROGRAM PEMBERIAN MAKANAN TAMBAHAN TERHADAP KEADAAN GIZI ANAK-ANAK PRA-SEKOLAH DI LINGKUNGAN KEBON KELAPA BOGOR - Darwin Karyadi; Ignatius Djokosusanto; S. Hasnah Soetedjo; Jajah K. Husaini; Dradjat D. Prawiranegara (Persagi, 1971)
Pengaruh program pemberian makanan tambahan terhadap keadaan gizi anak2 prasekolah di Lingkungan Kebon Kelapa, Bogor. (The effect of food supplementation program on the nutritional status of pre-school children). Presented at the Second National Pediatric Congress. Bandung. 1971. One of the main nutrition problems in developing countries is protein calorie malnutrition. The age group that has been most affected is the pre-school child. Serious dietary deficiency will impair his physical and mental developments. The pilot project was designed for the care of pre-school children with signs of malnutrition through a supplementary feeding program. The approach is to educate mothers on how to feed, with locally available foods, and care for their pre-school children; using techniques that are compatible with their understanding and financial limitation through active participation. The duration of the supplementary feeding program was three months. In order to evaluate the program some anthropometric measurements, dietary intake study and clinical assessment were carried out before and after the program. The results of the study reveal that this program-approach can be recommended in the prevention and in combating malnutrition in the pre-school child.